Dyke Architecture, Mineral Layering, and Magmatic Convection; New Perspectives From the Younger Giant Dyke Complex, S Greenland. (1st March 2022) - Koopmans, L.; McCarthy, W.; Magee, C.
Abstract: Igneous sheet intrusions are a fundamental component of volcano plumbing systems. Identifying how sheet intrusion emplacement and geometry controls later magmatic processes is critical to understanding the distribution of volcanic eruptions and magma‐related ore deposits. Using the Younger Giant Dyke Complex (YGDC), a Mesoproterozoic suite of large (<800 m wide) mafic dykes in southern Greenland, we assess the influence sheet of emplacement and geometry on subsequent magma flow and mush evolution. Through structural mapping, petrographic observations, and anisotropy of magnetic susceptibility fabric analyses, we show that the YGDC was emplaced as a series of individual dyke segments, which following coalescence into a sheet intrusion remained largely isolated during their magmatic evolution. Through petrographic evidence for liquid‐rich growth of cumulus phases, concentric magnetic fabrics, and the detailed study layered zones within the YGDC, we infer magma convection occurred within the cores of each dyke element. We particularly relate layering to hydrodynamic sorting processes at a magma‐mush boundary toward the base of each convection cell. Overall, our work demonstrates that the initial geometry of sheet intrusions can constrain magma flow patterns and affect the distribution of crystallization regimes. Key Points: The Younger Giant Dyke Complex (<800 m wide, 150 km long), S Greenland was emplaced as a series of isolated segments Petrography and anisotropy of magnetic susceptibility fabrics identify segments behaved independently, even after segments coalesced Igneous layering formed through hydrodynamic processes at the magma‐mush boundary, and crystallization occurred in a convecting system